Diffuse infrared indoor communication system - New, Wei Lee. (2008)
This thesis reports on the feasibility, design considerations of construction of a high-speed infrared communication link using inexpensive Light-Emitting-Diodes (LEDs). System configuration is non-directed line of sight (LOS) with single element receiver. The speed of the system constructed is 20 MHz (40 Mbps for on-off keying). This report covers four main aspects. Firstly, the simulation program written to model power distribution of LEDs through tilting is discussed. Experimental results obtained from the measurements are verified to be within experimental errors. Secondly, the design considerations in the transmitter are discussed, with speed response of LEDs and the driving circuitry covered in detail. Following that, the design considerations in high-speed low-noise optical receiver's construction using IC chips are covered in detail. Finally, a shielding cover for the receiver is constructed and the shielding effectiveness is discussed in this report.